2015
DOI: 10.1016/j.eucr.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

BCG Induced Necrosis of the Entire Bladder Urothelium

Abstract: Instillation therapy with attenuated tuberculosis bacteria (BCG) can significantly reduce rates of recurrence of non-muscle invasive bladder cancer. Local and systemic side effects such as dysuria, irritative voiding symptoms or partial bladder contracture and systemic inflammation were reported. A 75 year-old male patient with recurrent non muscle invasive bladder cancer developed necrosis of the entire bladder urothelium more than six years after BCG instillation immunotherapy. The resulting irritative voidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…We hypothesized that there are unknown effects of intravesical instillation resulting in complications, including anatomical modifications such as mucosal changes in the bladder and deterioration of immunity after performing transurethral resection of the bladder several times before intravesical instillation or intravesical instillation. In fact, bladder contracture or necrosis has been reported with local side effects after BCG intravesical instillation, 21 and a previous study found that BCG intravesical instillation causes modulation of peripheral immune mechanisms in addition to local immune activation 22…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that there are unknown effects of intravesical instillation resulting in complications, including anatomical modifications such as mucosal changes in the bladder and deterioration of immunity after performing transurethral resection of the bladder several times before intravesical instillation or intravesical instillation. In fact, bladder contracture or necrosis has been reported with local side effects after BCG intravesical instillation, 21 and a previous study found that BCG intravesical instillation causes modulation of peripheral immune mechanisms in addition to local immune activation 22…”
Section: Discussionmentioning
confidence: 99%
“… 2 Krönig et al reported BCG-induced necrosis of the entire bladder urothelium in 2015. 3 To our knowledge, this is the first report on BCG intravesical instillation therapy-induced urothelium necrosis of both the bladder and upper urinary tract. Although there were no obvious recurrences, surgical treatment alleviated severe symptoms and progressive postrenal failure and improved the patient's quality of life.…”
Section: Informed Consent Was Obtained From the Patient For The Publi...mentioning
confidence: 79%
“…2 ). As a result, a total of 15 cases with detailed cystoscopic and pathologic descriptions from 14 studies were identified [ [8] , [9] , [10] , 16 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. The clinical characteristics of the selected cases were summarized in Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%